The Drama of Living Becoming Wise in the Spirit - Ford, David F. (Grand Rapids, Michigan BrazosPress, 2014)
How can we live wisely in the twenty-first century, alert to God and to other people amid the ups and downs of modern life' We find ourselves in the middle of complex situations, relationships, responsibilities, ongoing dramas, and challenges. Our respo
Keywords: Christian life. Christianity and culture. Christianity -- 21st century